1995
DOI: 10.1128/jvi.69.9.5787-5790.1995
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding site-deleted foot-and-mouth disease (FMD) virus protects cattle from FMD

Abstract: Binding of foot-and-mouth disease virus (FMDV) to cells requires an arginine-glycine-aspartic acid (RGD) sequence in the capsid protein VP1. We have genetically engineered an FMDV in which these three amino acids have been deleted, producing a virus particle which is unable to bind to cells. Cattle vaccinated with these receptor binding site-deleted virions were protected from disease when challenged with a virulent virus, demonstrating that these RGD-deleted viruses could serve as the basis for foot-and-mouth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 19 publications
1
28
1
Order By: Relevance
“…However, this approach is cumbersome and needs virus handling. Further, it was also shown that receptor binding site-deleted FMDV protected cattle from FMD (18). The synthetic peptide of sequence 141-160 alone was shown to protect G.pigs against viral challenge (6,19).…”
Section: Discussionmentioning
confidence: 96%
“…However, this approach is cumbersome and needs virus handling. Further, it was also shown that receptor binding site-deleted FMDV protected cattle from FMD (18). The synthetic peptide of sequence 141-160 alone was shown to protect G.pigs against viral challenge (6,19).…”
Section: Discussionmentioning
confidence: 96%
“…Wild-type FMDV type A12 and the genetically engineered chimera expressing the serotype O1 VP1 G-H loop substituted for the equivalent portion of the A12 capsid were derived from infectious cDNAs pRMC35 (32) and pRM-A/O (30), respectively. All pcDNA3based plasmids were prepared by using viral cDNA from pRMC35 (32) and pRM-RGD Ϫ (21). The virus used to challenge swine was a bovine passage 78 preparation of a type A12 Vallee strain 119 isolate (21).…”
Section: Methodsmentioning
confidence: 99%
“…Although it is unclear where this disparity arises, the importance of antibodies to epitopes present on other portions of the capsid in conferring protection to livestock (20,30) and the intrinsic variability of the virus (8) could explain why peptide vaccines do not protect as well as whole capsid-based vaccines (35). To produce a new generation of safer FMD vaccines, we have used genetic engineering to develop attenuated FMD virions (21,26). In one case, attenuation has been achieved by removing the coding region for a viral proteinase, L, that is responsible for inhibition of translation of host-cell mRNAs during infection (4,18,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This exposed segment contains the cell adhesion tripeptide arginine-glycine-aspartic acid (RGD), a wellknown integrin-binding ligand (Ruoslathi and Pierschbacher, 1987), 60 copies of which are symmetrically displayed at the capsid surface around the five-fold axis. In FMDV, the RGD peptide has been proposed to be the unique cell attachment site on the virus surface because its absence abolishes infectivity (McKenna et al, 1995). Because RGD-containing peptides also promote internalization of different natural and recombinant viruses (Hart et al, 1994;Wickham et al, 1993), this stretch might serve for both cell recognition and FMDV entry through the formation of receptosomes.…”
Section: Introductionmentioning
confidence: 99%